Time‐varying risk of rare disasters, investment, and asset pricing. Issue 3 (3rd February 2020) - Liu, Bo; Niu, Yingjie; Yang, Jinqiang; Zou, Zhentao
Abstract: We extend an equilibrium business cycle/asset pricing model of production and capital accumulation by introducing a time‐varying risk of rare disasters. It predicts that investment is much more volatile than output, which provides theoretical support for the empirical data. Furthermore, the model‐generated stationary distribution of the investment‐output ratio fits the data remarkably well. Both of them exhibit negative skewness, which means that there is a small probability that this ratio can be very low. Given the observations of the investment‐output ratio, we obtain the values of the jump intensity implicit in the historical data and find those recession periods coincide with a rapid increase in the probability of a disaster. Finally, the model shows that the existence of adjustment costs generates a procyclical price of capital and contributes to resolving the equity premium puzzle.